Practical guide to pesticides and their use - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Food crop protection in West and Central Africa: a practical guide to use of pesticides in countries with savannah and humid forest by Jean-Gilbert Theissen and Roland Pierrot 1994 525pp ISBN 2 11 088570 X (Pbk)